Development and psychometric evaluation of postgraduate nursing student academic satisfaction scale - Pardis Rahmatpour; Hamid Peyrovi; Hamid Sharif Nia (Wiley, 2021)
Abstract Aim To develop and evaluate the psychometric properties of postgraduate nursing student academic satisfaction scale (PNSASS). Design The mixed‐method study was carried out in two phases; (a) item generation by hybrid concept analysis and (b) item reduction by psychometric evaluation of the developed scale. Methods The initial item pool (N = 209) was prepared based on concept analysis results and similar instruments. A total of 402 postgraduate nursing students willingly participated in online data gathering from August 2019 to May 2020. The validity (face, content and construct) and reliability (stability and internal consistency) of the scale were assessed. Results Exploratory factor analysis identified that the scale had four factors which explained 64.80% of the total extracted variance. The results of confirmatory factor analysis showed a good model fit. The reliability of scale was strong to excellent. The results showed that the PNSASS has suitable validity and reliability properties, which can be used to measure the academic satisfaction of postgraduate nursing students.